2020
DOI: 10.21203/rs.2.22544/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Response of phytohormone mediated plant homeodomain (PHD) family to abiotic stress in upland cotton (Gossypium hirsutum spp.)

Abstract: Abstract Background: The sequencing and annotations of cotton genomes provide powerful theoretical support to unravel more physiological and functional information. Plant homeodomain (PHD) protein family has been reported to be involved in regulating various biological processes in plants. However, their functional studies have not yet been carried out in cotton. Results: In this study, 108, 55, and 52 PHD Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…The gain or loss of key motifs as species evolved may have resulted in changes to protein functions that altered plant development. Phytohormones and abiotic stresses might affect fiber development through signal transduction pathways (Chen et al 2019;He et al 2019;Cheng et al 2020;Wang et al 2020a, b;Zhang et al 2020;Tian and Zhang 2021;Wu et al 2021). We identified numerous cisacting elements responsive to light, phytohormones, defense processes, and stress as well as multiple TF-binding sites upstream of transcriptional start sites.…”
Section: Discussionmentioning
confidence: 80%
“…The gain or loss of key motifs as species evolved may have resulted in changes to protein functions that altered plant development. Phytohormones and abiotic stresses might affect fiber development through signal transduction pathways (Chen et al 2019;He et al 2019;Cheng et al 2020;Wang et al 2020a, b;Zhang et al 2020;Tian and Zhang 2021;Wu et al 2021). We identified numerous cisacting elements responsive to light, phytohormones, defense processes, and stress as well as multiple TF-binding sites upstream of transcriptional start sites.…”
Section: Discussionmentioning
confidence: 80%
“…Since Schinder first discovered and identified PHD proteins in plants (Schindler et al, 1993), an increasing number of PHDs have been reported. To date, 59 Oryza stiva members (Sun et al, 2017), 108 Gossypium hirsutum members (Wu et al, 2021), 72 Solanum tuberosum members (Qin et al, 2019), 60 Phyllostachys edulis members (Gao et al, 2018), and 67 Zea mays members (Wang et al, 2015a) have been identified. It is known that PHD proteins not only participate in the regulation of plant growth and development but also play an important role in stress response, especially to abiotic stresses such as salt, hightemperature, low-temperature, and drought stress.…”
Section: Introductionmentioning
confidence: 99%
“…Wei et al also found that Arabidopsis thaliana transgenic plants overexpressing soybean GmPHD2 exhibited higher salt resistance, possibly because overexpression of GmPHD2 enhanced the scavenging of oxidative substances (Wei et al, 2009). Furthermore, under abiotic stress, genes in the PHD-finger family in maize, cotton, and poplar show differential expression under salt, drought, and cold stress (Wang et al, 2015a;Wu et al, 2016;Wu et al, 2021). Thus, it can be seen that the PHD family genes play a crucial role in regulating plant resistance to stress.…”
Section: Introductionmentioning
confidence: 99%
“…Cotton is an important economic crop of the world and contributes largely to the textile industry. Different gene families such as GGPPS [ 23 ], LOG [ 24 ], BES1 [ 25 ], GH3 [ 26 ], GSK [ 27 ], GATL [ 28 ], GhPHD [ 29 ] and GhAA1 [ 30 ] have been identified in cotton, but there is no published research about RAD gene family in cotton. Previous studies reported that RAD51 participate in DNA repair, homologous recombination and genome stability.…”
Section: Discussionmentioning
confidence: 99%